2015
DOI: 10.5815/ijmecs.2015.09.01
|View full text |Cite
|
Sign up to set email alerts
|

Effect of GameMaker on Student Attitudes and Perceptions of Instructors

Abstract: Abstract-Computational thinking including the ability to think critically and solve problems provides benefits for every career path. A positive attitude toward computer science can increase the possibility of students selecting courses that increase computational thinking or pursuing computer science (CS) as a major. This research examined the effect of using GameMaker on the attitudes of students toward computer science (CS) and CS instructors in an introductory CS course. The research consisted of an initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
1
0
0
Order By: Relevance
“…Students were more engaged and willing to explore the connection between the ERDs and relational schemas. These findings are consistent with the previous research that visualization helps to get students' attention [7,10,12,13,24]. In addition, the students' feedback also indicated that the visualization tool facilitated their understanding of the ER model and its connection to the relational model.…”
Section: Discussionsupporting
confidence: 90%
“…Students were more engaged and willing to explore the connection between the ERDs and relational schemas. These findings are consistent with the previous research that visualization helps to get students' attention [7,10,12,13,24]. In addition, the students' feedback also indicated that the visualization tool facilitated their understanding of the ER model and its connection to the relational model.…”
Section: Discussionsupporting
confidence: 90%